Glucose Starvation-Caused Oxidative Stress Induces Inflammation and Autophagy in Human Gingival Fibroblasts - Runbo Li; Hirohito Kato; Yoichiro Taguchi; Xin Deng; Emika Minagawa; Takaya Nakata; Makoto Umeda (MDPI AG, 2022)
Gingival tissue experiences an environment of nutrient shortage, such as low glucose conditions, after periodontal surgery. Our previous studies found that this low glucose condition inhibits normal gingival cell functions. However, the mechanism by which this glucose-deficient environment causes cellular damage to human gingival fibroblasts (HGnFs) remains unclear. This study aimed to investigate the biological effects of ROS induction on HGnFs under low glucose conditions. ROS levels and cellular anti-ROS ability of HGnFs under different glucose concentrations were evaluated by measuring ROS formation and the expression of superoxide dismutase and heme oxygenase 1. Changes in cellular viability were investigated using 5-bromo-2'-deoxyuridine assay and cell survival detection, and the cellular damage was evaluated by the expression of inflammatory cytokines and changes in the expression of autophagy-related protein. ROS formation was then blocked using N-acetyl-L-cysteine (NAC), and the effects of ROS on HGnFs under low glucose conditions were investigated. Low glucose conditions induced ROS accumulation, reduced cellular activity, and induced inflammation and autophagy. After NAC application, the anti-ROS capacity increased, cellular activity improved, and inflammation and autophagy were controlled. This can be effectively controlled by the application of antioxidants such as NAC.